Pengaruh Iklan dan Influencer di Aplikasi Tiktok Terhadap Minat Beli Konsumen (Studi Kasus Pada Mahasiswa STIS Al-Wafa Bogor) - Salsabila, Syauqiah; Rahmawati, Desi; Wibowo, Finantyo Eddy (Universitas Labuhanbatu, 2023)
The increasingly widespread use of Tiktok social media in adolescents in Indonesia will certainly greatly affect one of the stages of adolescent development, namely self-confidence. Having self-confidence is very important because a teenager will be able to assess himself and do a job effectively in his life. This study aims to determine the influence of pleasure perception, benefit perception, and ease of use perception on the intention to use the tiktok application This study used a quantitative approach with data collection methods through online questionnaires and was determined using non-probability purposive sampling methods. The data was obtained by distributing online questionnaires to 100 STIS Al Wafa students who used the Tiktok application. The results of this study will later show how much influence advertisements and influencers on the Tiktok application have on the buying interest of people who use the application. however, the perception of pleasure of Tiktok content has a positive and significant effect on the perception of benefits, perception of ease of use and intention to use the Tiktok application. The results of these findings can be used as a reference for future research. The main theory in this study uses the Technology Acceptance Model (TAM) which is used to explain the relationship between perception of pleasure, perception of benefits, perception of ease of use and intention to use. A limitation of this study is the intention variable to use the Tiktok application which shows that the R-Square score is 0.488 or 48.8% so that the variable is still not explained well and adequately by the antecedent variable. This study contributes to the literature on the topic of social media use by considering the variables of pleasure perception, benefit perception and ease in influencing the intention to use Tiktok.`